Desert jewels : cactus flowers of the Southwest and Mexico - Schaefer, John Paul, 1934- (Sentinel Peak, an imprint of The University of Arizona Press, 2023)
"Cactus flowers are jewels of the desert-they add brilliant pops of color to our arid surroundings. In this book, renowned Tucson photographer, John P. Schaefer, brings the exquisite and unexpected beauty of the cactus flower to the page. In 300 plus close-up photographs of cactus flowers native to the U.S. Southwest and Mexico, one experiences a visual feast of color and texture, nuance and light. The photographs allow the casual viewer to appreciate the spectacular range of color and form cactus flowers have to offer. For the cactus enthusiast, the book offers a comprehensive collection of high-quality flower photographs available nowhere else. The photographs include approximately 235 cactus species organized by family. The book starts with an Introduction by John P. Schaefer that is both autobiographical and informative. It offers a glimpse into his process for capturing these elusive desert gems as well as the notoriety his cactus flower photography gained after being featured as a book of stamps issued by the U.S. Postal Service"--